Analysis of Management System Implementation Occupational Health and Safety (SMK3) at Hospital Royal Prima Medan 2018 - Diana Agustina Ritonga; Sri Lestari Ramadhan; Ermi Girsang; Sri Wahyuni Nasution (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Based on data from BPJS Employment for North Sumatra (Sumbagut), the number of BPJS Employment accidents in 2016 reached an average of 226 cases per day. Implementation of Occupational Safety and Health Management (SMK3) at RSU Royal Prima Medan in 2018. The study was conducted in November-December 2018. The sample in this study amounted to 5 people. The type and design of this research are qualitative. The results of the research, commitments, and policies of SMK3 at the Royal Prima Hospital Medan have been carried out with written decisions regarding K3, the planning which was prepared directly by the leader of the Royal Prima Medan Hospital orally already exists and has been fully realized, the organization and implementation are carried out verbally comprehensive and significant so that all workers are controlled for their health and minimize the occurrence of work-related accidents, the implementation of SMK3 is by participating in K3 training, Royal Prima Hospital Medan also requires Personal Protective Equipment (PPE) in the occupational health and safety management system, the organization has been made but not running optimally. Royal Prima Hospital is expected to further improve the implementation of SMK3RS, make a thorough improvement of SMK3 and review SMK3 documents.